Isolation of vaccinia virus mutants capable of replicating independently of the host cell nucleus. - Villarreal, E C (J Virol, 1984)
alpha-Amanitin-resistant vaccinia virus mutants were isolated after serial viral passages in BSC-40 cells that were carried out in the presence of inhibitory levels (6 micrograms/ml) of alpha-amanitin. One such mutant, alpha-27, was highly refractory (greater than 95%) to alpha-amanitin-mediated inhibition and was selected for further study. In the absence of drug, the phenotypes of alpha-27 and wild-type vaccinia virus were indistinguishable with respect to growth kinetics. DNA synthesis, protein synthesis, and morphogenesis. Infections in the presence of alpha-amanitin revealed two striking differences, however. First, wild-type virus was unable to catalyze proteolytic processing of the two major capsid proteins VP62 and VP60, whereas alpha-27 was most efficient at this process. Second, wild-type viral morphogenesis within the infected cells was arrested by alpha-amanitin at an apparently analogous step to that previously described for enucleated cells. This observation was supported by the ability of alpha-27 virus to replicate in enucleated BSC-40 cells. Restriction enzyme analyses of alpha-27 versus wild-type genomes revealed that a XhoI cleavage site was altered in the alpha-27 DNA molecule, suggesting a possible location for the alpha-amanitin resistance locus. IMAGES: